Development and evaluation of polyherbal formulation for memory enhancement: study on its antioxidant properties and synergistic effects - Zainol Abidin, N.A; Kormin, Faridah; Anuar, Mohamed; A.F., N. (Rynnye Lyan Resources, 2020)
Centella asiatica, Piper sarmentosum and Morinda citrifolia is well-known for their memory enhancement contribution from traditional practices as well as recent researches. However, all three herbs are utilized individually and never mixed together. The nutrient data on the synergistic effect on all three herbs remain scarce. The aims of this research project were to apply Simplex-centroid mixture design in describing the study for the effect of polyherbal formulation on antioxidants properties and its synergistic effects. Based on results obtained, there was a significant difference in antioxidant properties of the polyherbal formulation. The results show the polyherbal formulation 3 and 13 (M. citrifolia only) has the highest antioxidant capacity when being tested with total phenolic content (TPC) (210.10 and 209.12 μg GAE/mL respectively) and 2,2-diphenyl-1- picrylhydrazyl (DPPH) (42.94 and 37.77%) assays. Contradict to this result, the highest in total flavonoid content (TFC) and 2,2-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) for describing antioxidant properties are formulations 1 and 11 (C. asiatica only). The TPC for formulation 1 and 11 are 479.8 μg RE/mL and 470 μg RE/mL respectively while ABTS radical inhibition for formulation 1 and 11 are 64.53% and 60% respectively. For ferric reducing ability of plasma (FRAP) assay, formulation 7 (2.11 μg FSE/mL) is the highest which have 1:1:1 ratio of each herb. In addition, TPC, TFC, and DPPH assays showed high antioxidant activities when only single herbs were added into the formulation. Meanwhile, ABTS and FRAP are prone to binary polyherbal formulation. Hence, this study showed an antagonism effect instead of synergistic effect since single formulation exhibited the highest for TPC, TFC and DPPH. All tests gave the lowest antioxidant properties when the mix was ternary polyherbal formulation.